EFEKTIVITAS MEDIA NEARPOD DALAM MEMAHAMI EJAAN YANG DISEMPURNAKAN (EYD) PADA KELAS XII LEMBAGA LES ATTAUFIQ - Qotrunnada, Anisah (Jurnal Komposisi, 2023)
Nearpod media is a learning media that is easily accessible so that nearpod learning media is very interesting when used in a lesson. The nearpod media consists of various features. Researchers in this study created Nearpod learning media with various features, such as material explanation videos, open questions, quizzes, hiking time, and pairs. The subject of this study is the effectiveness of Nearpod learning media in understanding Enhanced Spelling (EYD). The object of research in class XII Private Les Attaufiq. This study used a qualitative descriptive method and collected data in the form of a questionnaire. The purpose of this study was to determine the effectiveness of Nearpod learning media in understanding Enhanced Spelling (EYD) in class XII Attaufiq Private Lessons. The results showed that nearpod learning media was very effective in understanding Enhanced Spelling (EYD). The results of the data show that the nearpod media is interesting, and EYD learning with the nearpod media is not boring. Apart from that, in understanding EYD, the nearpod media is actually very helpful and the nearpod media is a learning media that is suitable for understanding Enhanced Spelling (EYD) guidelines because there are several features, one of which is Time to Climb which many people like.